Development of multi-purpose 3D printed phantoms for MRI. (29th March 2019) - Rai, Robba; Wang, Yu Feng; Manton, David; Dong, Bin; Deshpande, Shrikant; Liney, Gary P
Abstract: This work describes the development and application of 3D printed MRI phantoms. Unlike traditional phantoms these test objects are made from solid materials which can be imaged directly without filling. The models were manufactured using both MRI visible and invisible materials. The MRI visible materials were imaged on a 3T system to quantify their T 1 and T 2 properties and CT to quantify the electron density. Three phantoms are described: a distortion phantom was imaged on an open bore MRI system to assess distortion over a 30 cm field-of-view; a solid tumour model was imaged using a motion simulator and compared to a standard water phantom to assess reduction in artefacts; finally, a test object created for textural analysis was evaluated on two 3T systems and reproducibility was assessed. Material 1 was the main material used in all phantom models and has a T 1 and T 2 of 152.3 ± 3.7 ms and 56.7 ± 2.5 ms and a CT density of 127.9 HU. Material 2 had a CT density of 115.1 HU and material 3 had a T 1 and T 2 of 149.5 ± 2.9 ms and 68.8 ± 7.8 ms and CT density of 15.3 HU. Image tests demonstrated the suitability and advantage of each phantom over more traditional versions: a high density set of control points enabled a comprehensive measurement of geometric accuracy; sufficient signal with a reduction in artefact was observed in the motion phantom, and the texture model provided reproducible measurements with an ICC > 0.9 for over 76% of texture features. Three different phantoms have been successfully manufactured and used to demonstrate the application of 3D printable materials for MRI phantoms.